LncRNA-Smad7 mediates cross-talk between Nodal/TGF-β and BMP signaling to regulate cell fate determination of pluripotent and multipotent cells. Issue 18 (22nd September 2022) - Kong, Xiaohui; Yan, Kun; Deng, Pujuan; Fu, Haipeng; Sun, Hongyao; Huang, Wenze; Jiang, Shuangying; Dai, Junbiao; Zhang, Qiangfeng Cliff; Liu, Jun-jie Gogo; Xi, Qiaoran
Abstract: Transforming growth factor β (TGF-β) superfamily proteins are potent regulators of cellular development and differentiation. Nodal/Activin/TGF-β and BMP ligands are both present in the intra- and extracellular milieu during early development, and cross-talk between these two branches of developmental signaling is currently the subject of intense research focus. Here, we show that the Nodal induced lncRNA-Smad7 regulates cell fate determination via repression of BMP signaling in mouse embryonic stem cells (mESCs). Depletion of lncRNA-Smad7 dramatically impairs cardiomyocyte differentiation in mESCs. Moreover, lncRNA-Smad7 represses Bmp2 expression through binding with the Bmp2 promoter region via (CA)12 -repeats that forms an R-loop. Importantly, Bmp2 knockdown rescues defects in cardiomyocyte differentiation induced by lncRNA-Smad7 knockdown. Hence, lncRNA-Smad7 antagonizes BMP signaling in mESCs, and similarly regulates cell fate determination between osteocyte and myocyte formation in C2C12 mouse myoblasts. Moreover, lncRNA-Smad7 associates with hnRNPK in mESCs and hnRNPK binds at the Bmp2 promoter, potentially contributing to Bmp2 expression repression. The antagonistic effects between Nodal/TGF-β and BMP signaling via lncRNA-Smad7 described in this work provides a framework for understanding cell fate determination in early development.